Socioeconomic disparities in the receipt of palliative care in biliary tract cancers. Issue 28 (1st October 2022) - Abodunrin, Faith; Adeoye, Oluwatayo; Krishnan, Mridula; Silberstein, Peter T.; Tupper, Connor
Abstract : 80 Background: Biliary tract cancers are tumors arising from epithelial cells lining the biliary tract including the intrahepatic bile duct, extrahepatic bile duct, gall bladder, and ampulla of Vater. The incidence of biliary tract cancers has over the years. While there have been several advances in the diagnosis and treatment of biliary tract cancers, palliative treatment remains important in the management of these cancers. This study aims to analyze the patterns associated with the receipt of palliative care in patients with biliary tract cancers. Methods: We conducted a retrospective review of 150, 007 patients in the National Cancer Database diagnosed with biliary tract cancer between 2004-2018 using ICD-O3 codes. Chi-square tests were used to assess the differences between palliative care recipients and non-recipients. Logistic regression was used to assess which variables influence the likelihood of receiving palliative care. Statistical analyses were performed using SPSS. Results: The overall palliative care utilization amongst patients with biliary tract cancers was 13%. The use of palliative care in biliary tract cancers gradually increased over the years. Patients with gall bladder cancers were less likely to receive palliative care than those with intra-hepatic biliary duct cancers (OR 0.60 p < 0.001). Our study also found significant differences in the utilization of palliative care based on race. Blacks were less likely to use palliative care than whites (OR 0.89 p = 0.001). Hispanic patients were less likely to utilize palliative care than whites (OR 0.70 95% CI 0.64-0.76). There was no statistically significant difference between the use of PC between Whites and Asians (OR 1.04 95% CI 0.95-1.13 p < 0.441). Privately insured patients were less likely to receive palliative care than uninsured patients (OR 0.88 p = 0.029). There were no statistically significant differences between the receipt of palliative care in uninsured patients and Medicare or Medicaid patients (OR 0.98 p = 0.69; OR 1.00 p = 0.93). Patients belonging to households with a median income (> $63, 333) were less likely to receive palliative care than those in low-income (< $40, 000) household (OR 0.67 p < 0.001). There was an increased likelihood of receiving palliative care in patients from communities with higher educational status. Patients who received treatment at academic/research programs were more likely to receive palliative care than those at community cancer programs (OR 1.18 95% CI 1.08-1.29). Conclusions: Our study identified disparities in the receipt of palliative care in biliary tract cancers based on socioeconomic status. Blacks and Hispanics were less likely to receive palliative care than whites. Interestingly, uninsured patients were more likely to receive palliative care than privately insured patients. As part of quality improvement, future research should address the drivers behind these reported disparities.